'Cranking up', 'whacking up' and 'bumping up': X-ray exposures in contemporary radiographic practice. Issue 2 (May 2016) - Hayre, C.M.
Abstract: This article explores the use of X-ray exposures following the introduction of direct digital radiography (DDR). Radiographers are central to delivering optimum levels of ionising radiation whilst maintaining sound image quality for radiological interpretation. Yet do radiographers utilise X-ray exposures appropriately? An ethnographic methodology provides insight of two general radiographic environments in the United Kingdom (UK) using participant observation and semi-structure interviews. A central theme uncovered as part of a Doctorate of Philosophy (PhD) study was the lack of autonomy concerning X-ray exposures within the general imaging environment. The findings highlight 'how radiographers behave'. For example, some radiographers do not alter 'pre-set' X-ray exposures, arguably failing to produce images of optimum diagnostic quality. Secondly, radiographers acknowledge 'whacking up', 'cranking up' and 'bumping up' X-ray exposures ensuring image production. In conclusion this article provides an original insight into the attitudes and behaviours of radiographers regarding X-ray exposures in contemporary practices using DDR. Dose and image optimisation are central tenets of radiographic practice that may be hindered in contemporary practices. Highlights: Identifies current use of X-ray exposures using direct digital radiography (DDR). Identifies that radiographers may rely on 'pre-set' X-ray exposures, facilitating 'dose creep'. Radiographers acknowledge the ability to deliberately increase X-ray exposures using DDR.